ALGEBRAIC PROOF IV FERMATS LAST THEOREM - Joseph, James E (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The special case z4 = x4 + y4 is impossible [1]. In view of this fact, it is only necessary to prove, if x, y, z, are relatively prime positive integers, Ï€ is an odd prime, zÏ€ = xÏ€ +yÏ€ (In this article, the symbol Ï€ will represent an odd prime). Also, a new proof is given that z4 = x4 + y4 is impossible.